Evidence-based medicine in primary care: qualitative study of family physicians - Dantas Guilherme; Tracy C Shawn; Upshur Ross EG (BMC Family Practice, 2003)
Abstract Background The objectives of this study were: a) to examine physician attitudes to and experience of the practice of evidence-based medicine (EBM) in primary care; b) to investigate the influence of patient preferences on clinical decision-making; and c) to explore the role of intuition in family practice. Method Qualitative analysis of semi-structured interviews of 15 family physicians purposively selected from respondents to a national survey on EBM mailed to a random sample of Canadian family physicians. Results Participants mainly welcomed the promotion of EBM in the primary care setting. A significant number of barriers and limitations to the implementation of EBM were identified. EBM is perceived by some physicians as a devaluation of the 'art of medicine' and a threat to their professional/clinical autonomy. Issues regarding the trustworthiness and credibility of evidence were of great concern, especially with respect to the influence of the pharmaceutical industry. Attempts to become more evidence-based often result in the experience of conflicts. Patient factors exert a powerful influence on clinical decision-making and can serve as trumps to research evidence. A widespread belief that intuition plays a vital role in primary care reinforced views that research evidence must be considered alongside other factors such as patient preferences and the clinical judgement and experience of the physician. Discussion Primary care physicians are increasingly keen to consider research evidence in clinical decision-making, but there are significant concerns about the current model of EBM. Our findings support the proposed revisions to EBM wherein greater emphasis is placed on clinical expertise and patient preferences, both of which remain powerful influences on physician behaviour.